Therapeutic strategies: Surgery for human papillomavirus‐associated oropharyngeal carcinoma. Issue 6 (30th September 2021) - Mclean, Timothy; Fitzgerald, Conall; Boyle, Jay O.
Abstract: Treatment of oropharyngeal cancer (OPC) has undergone considerable evolution since the discovery of human papillomavirus (HPV)‐associated OPC. It is widely understood that HPV OPC affects a younger population and standard treatment offers improved oncologic outcomes compared with non‐HPV OPC but can cause significant toxicities and long‐term side effects. Surgery for treatment de‐escalation is an active area of research. The purpose of this review is to explore surgery as it relates to the treatment of HPV OPC with a focus on the evolution of treatment, rationale for surgery, surgical techniques, outcomes, and the role of surgery in de‐escalation of treatment.